Factors Associated with Low Back Pain in Pre-Clinical Students in the Faculty of Medicine at Pelita Harapan University: Original Research - Samudra, Edeline; Kalumpiu, Jane Florida (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Low back pain is one of the most common health problems globally, including in Indonesia, and can result in limitations on a person's activities. While low back pain is typically associated with adults and the elderly, its prevalence is also notably high among students, particularly medical students. Despite the various factors contributing to low back pain, there is limited data on its prevalence and associated factors in Indonesia.Methods: A cross-sectional study was conducted at the Faculty of Medicine, Pelita Harapan University, utilizing consecutive sampling. Data were collected using the Nordic Musculoskeletal Questionnaire, Pittsburgh Sleep Quality Index (PSQI), International Physical Activity Questionnaire (IPAQ), and Perceived Stress Scale (PSS).Results: Out of 179 students, 144 (80%) experienced low back pain, while 35 (20%) did not. Among students with low back pain, 1.4% had psychological history, 7.3% had history of spinal problems, 0.7% had family history, 15.3% were obese, 75% had poor sleep quality, 8.3% had high-risk physical activity, 6.9% had a high-risk position, and 7.6% had a high-risk stress level. While other factors showed no significant association with low back pain, sleep quality demonstrated a significant association with a p-value of 0.022 (OR 2.52, CI 1.18-5.43).Conclusion: There is a significant association between sleep quality and low back pain in pre-clinical medical students at UPH, while other factors did not exhibit significant correlations.